2021
DOI: 10.3389/fimmu.2021.720393
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota, Probiotics, and Their Interactions in Prevention and Treatment of Atopic Dermatitis: A Review

Abstract: Atopic dermatitis (AD) is a public health concern and is increasing in prevalence in urban areas. Recent advances in sequencing technology have demonstrated that the development of AD not only associate with the skin microbiome but gut microbiota. Gut microbiota plays an important role in allergic diseases including AD. The hypothesis of the “gut-skin” axis has been proposed and the cross-talk mechanism between them has been gradually demonstrated in the research. Probiotics contribute to the improvement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 145 publications
0
92
1
4
Order By: Relevance
“…Elevated fecal caproic acid levels suggest altered gut microbial communities in infants with allergic symptoms [ 26 , 27 ]. Experimental data [ 28 ] had showed that the intestinal bifidobacteria, gram-positive aerobic bacteria and enterococci were relatively few, but children with a high number of Clostridium and Staphylococcus aureus are prone to allergic symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated fecal caproic acid levels suggest altered gut microbial communities in infants with allergic symptoms [ 26 , 27 ]. Experimental data [ 28 ] had showed that the intestinal bifidobacteria, gram-positive aerobic bacteria and enterococci were relatively few, but children with a high number of Clostridium and Staphylococcus aureus are prone to allergic symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Several review articles about probiotics and gut microbiota with AD were already published and should be considered. Fang et al [ 28 ] have focused on the the potential mechanisms of probiotics on alleviating AD via upregulation of epidermal barrier and regulation of immune signaling, and the possible effective substances on AD, which provide the supports for targeting gut microbiota to AD prevention and treatment. Disamantiaji et al [ 69 ] have included a total of 5 studies, and have concluded that probiotics supplementation in the management of eczema in children does not show a clinically relevant difference vs. standard treatment in reducing eczema severity.…”
Section: Discussionmentioning
confidence: 99%
“…For children with ASD, Xu et al summarized that the relative abundance of Bifidobacterium was lower compared to controls (Xu et al, 2019). Even though several studies had revealed that Bifidobacterium was less in AD infants compared to healthy controls (Fang et al, 2021), controversy always exists. A cross-sectional study from Brazil revealed that AD children had a greater abundance of Bifidobacterium (OR: 11.09; 95% CI: 2.14; 57.39) (Melli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These topics included the microbiome and probiotics. The roles played by the microbiological environments of the skin and other organs (e.g., the gut) remain poorly understood, as do the effects of probiotics [ 9 ]. As patients are now increasingly exposed to commercial probiotics, any abnormal changes in the composition or functions of the AD microbiome require attention, as do any effect of probiotics on AD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the clinical evaluation and management of AD remain challenging [ 8 ]. Recently developed drugs (dupilumab, oluminant, and rinvoq), a growing interest in patient quality of life, and new potential therapeutic targets (such as the gut and skin microbiomes [ 9 , 10 , 11 , 12 , 13 , 14 ]) have motivated researchers to intensify their current approaches and explore new areas of AD research.…”
Section: Introductionmentioning
confidence: 99%